Are Down syndrome children more vulnerable to tooth wear?. Issue 11 (24th July 2019) - Hyder, M.; Tanboga, I.; Kalyoncu, I.; Arain, H.; Marks, L.
Abstract: Background: An oral condition that has largely been ignored in the Down syndrome population is pathological tooth wear. This study is aimed to create more awareness of the reasons underlying the tooth wear observed in patients with Down syndrome and to suggest different methods to prevent this condition. This research also potentially serves as a platform for future researchers to perform an in‐depth analysis of the factors we identified. The aim of this study was to determine if children with Down syndrome are more prone to tooth wear than children who do not have Down syndrome. Methods: Our sample consisted of 120 children with Down syndrome who were compared with 120 children with no disabilities. The parents or guardians were asked to complete a questionnaire and a 3‐day diet chart, while the wear on each tooth was recorded using the standardised Simplified Smith and Knight Tooth Wear Index. Results: Children with Down syndrome experience tooth wear more frequently than non‐Down syndrome children. A history of asthma, mouth breathing and gastro‐oesophageal reflux disease as well as the intake of acidic diet and drinks has exerted significant effects on the prevalence of tooth wear. Conclusions: The early diagnosis and analysis of the underlying aetiology are important for the management of tooth wear in children with Down syndrome who have shown a greater tendency to develop erosive lesions.